REGIONAL DIALECTOLOGY (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Regional dialectology is the study of language variations across different geographical areas, focusing on how regional factors influence speech patterns. This research investigates the phonetic, lexical, and syntactic differences observed in distinct regions, aiming to understand how social, cultural, and historical contexts shape dialects. Using a combination of fieldwork and corpus analysis, data were gathered from native speakers across urban and rural communities within a defined region.